Enhancing the Students’ Ability to Integrate Mathematics Learning Management through Active Learning Activities - Busadee, Nutjira (e-Journal of Education Studies, Burapha University, 2023)
This paper presents a series of active learning activities aimed at enhancing students' ability to design and create integrated mathematics learning management across five thematic units: 1) Sports, 2) PISA, 3) Local Wisdom, 4) STEM, and 5) Philosophy of Sufficiency Economy. These activities encompass four teaching steps: 1) preparation, 2) exploration, 3) presentation, and 4) reflection. The study involved 20 mathematics major students enrolled in the first semester of the academic year 2022. The findings demonstrated that the students exhibited a high level of proficiency in designing and creating integrated mathematics learning management for each unit. The overall average score was 87.31%, indicating a commendable level of integration across different domains: STEM (96.0%), adherence to PISA guidelines (89.0%), integration of subjects and local wisdom (88.67%), integration within the sports context (84.0%), and integration of the philosophy of sufficiency economy (78.9%). The study strongly recommends focusing on active learning activities in each unit, such as group discussions, problem-solving exercises, interactive technology tools, and the utilization of educational games. These activities have shown the highest impact on students' abilities.